Vibration-assisted installation and decommissioning of a slip-joint. (15th April 2020) - Cabboi, Alessandro; Segeren, Maxim; Hendrikse, Hayo; Metrikine, Andrei
Highlights: The slip-joint is a promising alternative to the grouted connection in wind turbines. A sound connection is achievable through an applied oscillatory forcing. Settlement events are initiated by choosing specific forcing frequencies. The decommissioning is facilitated through an oscillatory forcing. Abstract: The structural failure of grouted connections for offshore wind turbines focused the industrial attention towards different and innovative solutions to guarantee a safe connection between the monopile foundation and the turbine tower. An alternative option to the traditional grouted joint is a direct steel-to-steel connection, also called a slip-joint which was sporadically used for onshore wind turbines. To such regard, a proof of concept is illustrated concerning a new installation and decommissioning technique of a slip-joint. The key aspect of the proposed method is to guarantee a proper fit and sound contact of the slip-joint by means of vibration-assisted settlements. Therefore, the effectiveness of applying a harmonic excitation during the installation and decommissioning procedure is experimentally investigated using a 1:10 scaled model of the slip-joint. During the dynamic tests, the applied static load and the settlements of the joint are monitored using load cells, displacement sensors and strain gauges placed both inside and outside the conical surfaces. For the installation tests, the results show that settlement occurs when applying a harmonic load at specific forcing frequencies. All the vibration-induced settlements tend to stabilize in time, indicating that a sound contact through vibration-assisted installation can be achieved. In a similar way, the decommissioning proved to be effective at certain forcing frequencies. According to all the tests performed during this experimental campaign, both the installation and decommissioning tests showed to be more sensitive to the forcing frequency rather than to the dynamic forcing amplitude.